A framework for the standardization of game analysis in ice hockey - Saunton, C. A.; Björklund, G. (International Journal of Sports Physiology and Performance, 2023)
Ice hockey is a global international team sport with 76 member countries of more than 1.6 million players registered in the International Ice Hockey Federation. Ice hockey games are characterized by explosive accelerations and decelerations on ice skates with frequent changes in speed and direction.1-3 These movement patterns occur repetitively in 30- to 90-second intervals (or "shifts") on ice, followed by a passive break of 3 to 5 minutes on the bench.4,5 Thus, ice hockey performance is unique because it is predominantly supported by anaerobic metabolism. Nevertheless, the aerobic system is important for recovery to generate repeated high-intensity on-ice performance.6,7